High-resolution MRI assessment of dactylitis in psoriatic arthritis shows flexor tendon pulley and sheath-related enthesitis. Issue 1 (26th September 2014) - Tan, Ai Lyn; Fukuba, Eiji; Halliday, Nicola Ann; Tanner, Steven F; Emery, Paul; McGonagle, Dennis
Abstract : Objective: Dactylitis is a hallmark of psoriatic arthritis (PsA) where flexor tenosynovitis is common. This study explored the microanatomical basis of dactylitis using high-resolution MRI (hrMRI) to visualise the small entheses around the digits. Methods: Twelve patients with psoriatic dactylitis (4 fingers, 8 toes), and 10 healthy volunteers (6 fingers, 4 toes) had hrMRI of the digits using a 'microscopy' coil and contrast enhancement. All structures were evaluated including the tendons and ligaments, related enthesis organs, pulleys, volar/plantar plates and tendon sheaths. Results: In dactylitis, collateral ligament enthesitis was seen in nine digits (75%), extensor tendon enthesitis in six digits (50%), functional enthesitis (5 digits, 42%), abnormal enhancement at the volar plates (2/5 joints, 40%) and the plantar plate (1/5 joints, 20%). Nine cases (75%) demonstrated flexor tenosynovitis, with flexor tendon pulley/flexor sheath microenthesopathy observed in 50% of all cases. Less abnormalities which were milder was observed in the normal controls, none of whom had any signal changes in the tendon pulleys or fibrous sheaths. Conclusions: This study provides proof of concept for a link between dactylitis and 'digital polyenthesitis' including disease of the miniature enthesis pulleys of the flexor tendons, further affirming the concept of enthesitis in PsA.